Valorization of manganese-containing groundwater treatment sludge by preparing magnetic adsorbent for Cu(II) adsorption. (15th April 2019) - Zhu, Suiyi; Lin, Xue; Dong, Ge; Yu, Yang; Yu, Hongbin; Bian, Dejun; Zhang, Lanhe; Yang, Jiakuan; Wang, Xianze; Huo, Mingxin
Abstract: Mn-containing sludge from groundwater treatment was converted to magnetic particles (MPs) via a one-step hydrothermal method using sodium ascorbate (SA) as the reductant. The MPs were characterized by X-ray diffraction spectroscopy, Mössbauer spectroscopy, X-ray fluorescence spectroscopy, magnetometry and Gran titration and the results showed that magnetic jacobsite was obtained as an intermediate product in transformation of Fe/Mn oxides to siderite and rhodochrosite. When the molar ratio of SA to Mn in the sludge was two, the produced MPs-2 contained a mixture of ferrihdyrite, hematite, jacobsite and Si/Al oxides, and could magnetize at 2.4 emu/g. Ferrihydrite content in MPs decreased with increase of the SA/Mn molar ratio, leading to decrease of the surface sites concentration (Hs ). Thus, MPs-2 contained optimized Hs of 6.7 mmoL/g and a desirable adsorption capacity of Cu(II) (73.1 mg/g). The adsorption isotherms of MPs-2 on Cu(II) complied with the Langmuir model and the adsorption kinetics fitted well with the pseudo-second-order model. The major mechanism of adsorption was cationic exchange of the coordinated H and Na ions on MPs-2 surface sites with the Cu(II) ions. This study was the first time to report preparation of MPs by recycling Mn-containing sludge, which could be used as a high-capacity and low-cost adsorbent in treatment of heavy metal-containing wastewater. Highlights: Magnetic adsorbent from Mn-containing sludge is effective to adsorb Cu(II). Chemisorption of the adsorbent's surface sites governed Cu(II) adsorption. Ferrihydrite content in the adsorbent is positively correlated to the total surface sites. Sorption properties of the adsorbents weakened with conversion of ferrihdyrite to jacobsite.